Pengembangan Modul Elektronik Tematik Berbasis Kontekstual Untuk Meningkatkan Keterampilan Berpikir Kritis Peserta Didik Kelas III UPT SDN 03 Negeri Batin - Siska Pratama Siska; Fatimatul Zuhroh Zuhroh (Institut Agama Islam Negeri Ponorogo, 2025)
The problem of this research originates from the results of the needs analysis on student learning. This study aims to produce contextual-based thematic e-module products that are appropriate and effective in improving students' critical thinking skills. This research is a type of research and developments (R&D) research. The development is carried out according to the theory of Borg & Gall. The population of this study was class III students of the Umpu Semenguk cluster. The sample of this research was determined by purposive sampling technique which was by following per under the research objectives and obtaining as many as 25 students. The data collection tool uses valid and reliable test instruments. The data analysis technique uses a paired t-test with calculation results of 0.00 or less than 0,005 in the class group before using the product and after using the product. Based on the data obtained from the results of the study, contextually based thematic e-modules to improve students' thinking skills are valid to use, contextually based thematic e-modules are effective in improving students' critical thinking skills Keywords: Critical Thinking Skills, Electronic Module, Contextual.